Strengthening Student Character From The Perspective Of Islamic Society Development - Bukhari Bukhari; Anwar Anwar (AL-UKHWAH - JURNAL PENGEMBANGAN MASYARAKAT ISLAM, 2026)
This study aims to analyze student character strengthening from the perspective of Islamic community development in the digital era. The crisis of student character emerges as a consequence of social transformation, globalization, and digitalization, which shifts values toward pragmatism and individualism. This research employs a qualitative approach through literature review and critical analysis of educational and social phenomena. The findings reveal that strengthening student character requires the integration of Islamic values such as honesty, trustworthiness, and responsibility through curriculum, campus culture, and spiritual development. The maqasid al-shariah approach provides a significant framework developing in character oriented toward public welfare. Therefore, character strengthening should not only be viewed as an educational project but also as part of a broader civilizational development within Islamic society